The doll in the garden : a ghost story - Hahn, Mary Downing (2007)
After Ashley and Kristi find an antique doll buried in old Miss Cooper's garden, they discover that they can enter a ghostly turn-of-the-nineteenth-century world by going through a hole in the hedge.
Keywords: Time travel -- Juvenile fiction; Ghost stories; Ghost stories; Fiction; Juvenile works; Ghost stories; Fiction